PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG SADARI - Muzayyaroh, Muzayyaroh; Suyati, Suyati (Jurnal Cakrawala Ilmiah, 2025)
Breast cancer is the most common type of cancer among women worldwide. Breast self-examination (BSE) is a method that can be carried out routinely and simply to detect any changes or abnormalities in the breasts. The percentage of adolescents who perform BSE can vary based on location, access to health information, and awareness of the importance of early detection. The aim of this research is to determine the level of knowledge and attitudes of female students regarding BSE. This type of research is descriptive research, namely describing the knowledge and attitudes of young women about BSE. In this study, the population was young women from the Ainusyam Dormitory, Darul Ulum Islamic Boarding School, Jombang. The location of this research is the Aiusyam dormitory at the Darul Ulum Jombang Islamic Boarding School, which will be carried out in July 2024. Data collection uses primary data using a questionnaire. The data that has been collected is processed with percentages and presented in diagram form. The results of this research obtained data on the level of knowledge of adolescent girls regarding BSE, mostly with a level of poor knowledge, namely 66%, sufficient knowledge of 27% and good knowledge of 7%. The attitude of young women regarding BSE mostly has a negative attitude, namely 59% and a positive attitude of 41%. The research results show that the level of knowledge and attitudes of young women regarding BSE still needs to be improved. The conclusion of this research is that the majority of respondents still have insufficient knowledge about BSE, and the majority of respondents have a negative attitude towards BSE. A comprehensive educational approach, involving various stakeholders, can help increase adolescent girls' knowledge and positive attitudes towards BSE, which in turn can contribute to early detection and reduction of mortality due to breast cancer.